Expression of the Heparan Sulfate Proteoglycan, Perlecan, during Mouse Embryogenesis and Perlecan Chondrogenic Activity In Vitro - French, M.M. (The Rockefeller University Press, 1999)
Expression of the basement membrane heparan sulfate proteoglycan (HSPG), perlecan (Pln), mRNA, and protein has been examined during murine development. Both Pln mRNA and protein are highly expressed in cartilaginous regions of developing mouse embryos, but not in areas of membranous bone formation. Initially detected at low levels in precartilaginous areas of d 12.5 embryos, Pln protein accumulates in these regions through d 15.5 at which time high levels are detected in the cartilage primordia. Laminin and collagen type IV, other basal lamina proteins commonly found colocalized with Pln, are absent from the cartilage primordia. Accumulation of Pln mRNA, detected by in situ hybridization, was increased in d 14.5 embryos. Cartilage primordia expression decreased to levels similar to that of the surrounding tissue at d 15.5. Pln accumulation in developing cartilage is preceded by that of collagen type II. To gain insight into Pln function in chondrogenesis, an assay was developed to assess the potential inductive activity of Pln using multipotential 10T1/2 murine embryonic fibroblast cells. Culture on Pln, but not on a variety of other matrices, stimulated extensive formation of dense nodules reminiscent of embryonic cartilaginous condensations. These nodules stained intensely with Alcian blue and collagen type II antibodies. mRNA encoding chondrocyte markers including collagen type II, aggrecan, and Pln was elevated in 10T1/2 cells cultured on Pln. Human chondrocytes that otherwise rapidly dedifferentiate during in vitro culture also formed nodules and expressed high levels of chondrocytic marker proteins when cultured on Pln. Collectively, these studies demonstrate that Pln is not only a marker of chondrogenesis, but also strongly potentiates chondrogenic differentiation in vitro.